Projetos de design entre universidades e empresa: diretrizes para favorecer a transferência de conhecimentos em design - Oliveira, Jóice Geisiane Müller (Universidade do Vale do Rio dos Sinos, 2019)
Within Innovation Systems, universities and industries are organizations that often intersect in the pursuit of knowledge and interorganizational projects. As an area of knowledge design presents a variety of approaches that can be put into practice in projects. Amid increasingly complex contexts, the way problems are addressed, how people are engaged in projects, and the execution of design projects themselves can contribute to innovation in organizations. The objective of this dissertation is to propose to universities, guidelines that favor the transfer of design knowledge in projects developed between university and industry. For the creation of the guidelines, a qualitative research was developed, through which the offering universities and industries demanding projects with design processes present in their scope were interviewed. Facilitators and barriers to the negotiation, contracting and development of these projects, as well as their perception of the transfer of design knowledge in these partnerships, were investigated with universities and companies. The analysis of the results presents ten dimensions that are associated with the offer, hiring and development of design projects between universities and companies. Based on the identified dimensions, the final result of this work is nine guidelines that can be adopted by universities in the construction of programs and strategies that favor the transfer of design knowledge in projects between university and industry.
Keywords: Estratégias em design; Desenvolvimento de novos produtos; Universidade-empresa; Diretrizes para projetos; Design strategies; New product development; University-industry; Project guidelines; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial